TREC-SAVE: a randomised trial comparing mechanical restraints with use of seclusion for aggressive or violent seriously mentally ill people: study protocol for a randomised controlled trial - Huf, Gisele (BioMed Central, 2011)
BACKGROUND: Thousands of people whose aggression is thought due to serious mental illness are secluded or restrained every day. Without fair testing these techniques will continue to be used outside of a rigorous evidence base. With such coercive treatment this leaves all concerned vulnerable to abuse and criticism. This paper presents the protocol for a randomised trial comparing seclusion with restraints for people with serious mental illnesses. METHODS/DESIGN: Setting-General psychiatric wards of a large psychiatric hospital in Rio de Janeiro, Brazil. Participants-Anyone aggressive or violent suspected or known to have serious mental illness for whom restriction is felt to be indicated by nursing and medical staff, but also for whom they are unsure whether seclusion or restraint would be indicated. Interventions-The standard care of either strong cotton banding to edge of bed with medications as indicated and close observation or the other standard care of use of a minimally furnished seclusion room but with open but barred windows onto the nursing station. Outcomes-time to restrictions lifted, early change of treatment, additional episodes, adverse effects/events, satisfaction with care during episode. Duration-2 weeks. Identifier: ISRCTN 49454276 http://www.controlled-trials.com/ISRCTN49454276